A low expansion silicon negative electrode material
By using porous carbon templates to load nanosilicon and coat conductive carbon and ionic conductor materials in the negative electrode material of lithium-ion battery, the problem of volume expansion of silicon materials during charging and discharging is solved, and high capacity density and good electrochemical performance are achieved. .
Patent Information
- Application Number
- CN202110093876.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-01-25
AI Technical Summary
During the charging and discharging of lithium-ion batteries, silicon materials have huge volume expansion due to lithium alloying, resulting in powderization, cracking and "island effect", which leads to continuous loss of irreversible capacity, limiting the industrial application of silicon-based materials.
Using porous carbon as a template, nanosilicon is loaded on the inside or surface of its pores to form a 3D interpenetrating structure, and conductive carbon and ionic conductor materials are formed on the surfaces of porous carbon and nanosilicon to optimize the pore structure to buffer the volume of silicon material. Expansion.
Through the combined structure of porous carbon and nano-silicon, the volume expansion of the silicon material is significantly buffered, the capacity density and electrochemical properties of the negative electrode material are improved, and the stability and safety of the material are enhanced.
Smart Images

Figure CN114792782B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials, and in particular relates to a low-expansion silicon negative electrode material. Background Art
[0002] In recent years, in order to meet the demand for multifunctional products, people have put forward higher and higher requirements on battery life, safety, fast charging and other performance. Silicon materials are considered to be new high-performance negative electrode materials for lithium-ion batteries due to their advantages such as high specific capacity, good safety and abundant raw material sources. However, during the charging and discharging process, silicon materials will produce huge volume expansion due to lithium alloying, causing the silicon active particles to pulverize and fail. At the same time, the cracking and pulverization of silicon particles causes poor electrical contact between active particles and current collectors, forming an "island effect". The repeated formation of new SEI films on the fracture surface induces the problem of irreversible continuous capacity loss, which restricts the industrial application of silicon-based materials. Summary of the invention
[0003] To solve the above problems, the present application provides a low-expansion silicon negative electrode material, which uses porous carbon as a template and loads nanosilicon inside or on the surface of its pores to form a 3D interpenetrating structure. At the same time, conductive carbon and ion conductor material coatings are formed on the surface of the porous carbon and nanosilicon. The open and closed pores, pore size, porosity, etc. are optimized to provide a buffer space for the volume expansion of the silicon material during the charging and discharging process.
[0004] In some embodiments, the present application provides a low-expansion silicon negative electrode material, including porous carbon / graphite, nano-silicon, conductive carbon and ion conductor materials, the pores of the porous carbon / graphite include open pores and closed pores; taking the total number of the open pores and the closed pores as 100%, the number of the open pores accounts for 80~99.9%.
[0005] The beneficial effect of the present application is that, using porous carbon as a template, nano-silicon is loaded inside or on the surface of its pores, the porous carbon provides a continuous conductive electron channel, and the nano-silicon material ensures the high capacity density of the negative electrode material; the optimization of the open and closed pores, pore size, porosity, etc. of the porous carbon can greatly buffer the volume expansion of the silicon material. In addition, the outer surface of the porous carbon is also coated with a double layer of conductive carbon and ion conductor material layer, which can improve the electronic conductivity and ion conductivity on the one hand, and prevent the electrolyte from directly contacting the active substance on the other hand, thereby improving the electrochemical performance of the material.
[0006] Additional aspects and advantages of the embodiments of the present application will be described and shown in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is a schematic diagram of the structure of a certain embodiment of the present application;
[0008] Figure 2 This is a structural schematic diagram of another embodiment of the present application;
[0009] Figure 3 This is a schematic diagram of the structure of a certain embodiment of the present application;
[0010] Figure 4 It is a structural schematic diagram of another embodiment of the present application. DETAILED DESCRIPTION
[0011] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0012] In this application, amounts, ratios, and other numerical values are presented in a range format, and it should be understood that such range format is used for convenience and brevity and should be flexibly interpreted to include not only the values explicitly specified as range limits, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0013] In the claims and detailed description, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. Item A may include a single element or multiple elements, and item B may include a single element or multiple elements.
[0014] In this application, Dv50 is the particle size corresponding to when the cumulative volume percentage of the material reaches 50%.
[0015] The present embodiment provides a low-expansion silicon negative electrode material, comprising porous carbon, nano-silicon, conductive carbon and ion conductor material, wherein the pores of the porous carbon include open pores and closed pores, the open pores are used to accommodate the nano-silicon material, and the closed pores can be used to buffer the volume expansion of silicon; taking the total number of the open pores and the closed pores as 100%, the number of the open pores accounts for 80-99.9%, preferably 85-95%. If the number of the open pores is too small, too little nano-silicon material can be accommodated, which will affect the capacity density of the material.
[0016] In some embodiments, the pore diameter is 50~1000nm, wherein, taking the total volume of the pores as 100%, the pore diameter of the pores accounting for 50~80% by volume is 200~1000nm, preferably the pore diameter of the pores accounting for 50~70% by volume is 300~600nm. If the volume proportion is less than 50%, the embedded nano-silicon content is small and the material specific capacity is low. If the volume proportion is greater than 80%, the embedded nano-silicon content is large, the volume expansion is large, and the structure is prone to collapse. The pore diameter is greater than 200nm, which is conducive to the embedding of nano-silicon materials, and at the same time, a certain amount of pores can be left to buffer the volume expansion of silicon materials. If the pore diameter is greater than 1000nm, the porous carbon structure will be unstable and prone to collapse.
[0017] In some embodiments, the porosity of the porous carbon is 2-95%, preferably 10-80%. If the porosity is too small, it will affect the embedding of the nano-silicon material, thereby affecting the material capacity; if the porosity is too high, it will affect the electrical conductivity and structural strength of the material.
[0018] Specifically, the porous carbon can be prepared in the following manner: using SiO2, polystyrene, PMMA or its colloid as a template, using phenolic resin, furfuryl alcohol, asphalt, sucrose, benzene, divinylbenzene, polyacrylonitrile, ethylene as a carbon source, removing the template after high-temperature pyrolysis to obtain porous carbon, controlling the proportion of open and closed pores by reaction pressure, solid content, etc., and controlling the porosity and pore size by the proportion and particle size of the template.
[0019] In some embodiments, the nano-silicon covers at least a portion of the pore walls of the open pores and at least a portion of the surface of the porous carbon; the conductive carbon covers at least a portion of the surface of the silicon particles; and the ion conductor material covers at least a portion of the conductive carbon.
[0020] Figure 1 This is a structural diagram of an embodiment, wherein the porous carbon 1 contains closed pores 2 and open pores 3, the nano silicon 4 is coated on the pore walls of the open pores 3 and on the surface of the porous carbon 1, the conductive carbon 5 is coated on the surface of the nano silicon 4, and the ion conductor material 6 is coated on the surface of the conductive carbon 5. The porous carbon 1 provides a continuous conductive channel, the closed pores 2 can buffer part of the volume expansion, and the open pores 3 also reserve some pores to further alleviate the volume expansion and ensure a low expansion rate of the material; the nano silicon 4 ensures a high specific capacity of the material, the conductive carbon 5 further improves the electronic conductivity of the material, and the ion conductor 6 provides more ion conduction channels, while isolating the electrolyte to prevent the occurrence of side reactions.
[0021] Figure 2This is a structural schematic diagram of another embodiment, wherein the porous carbon 1 contains closed pores 2 and open pores 3, the nano-silicon 4 is coated on the pore walls of the open pores 3 and the surface of the porous carbon 1, the conductive carbon 5 is coated on the surface of the nano-silicon 4 and aggregated at the mouth of the open pores 3 to complete the pore sealing, the ion conductor material 6 is coated on the surface of the conductive carbon 5, and finally spherical silicon-containing particles are formed.
[0022] In some embodiments, the nano-silicon is filled in the open pores; the conductive carbon covers at least a portion of the surface of the porous carbon; and the ion conductor material covers at least a portion of the conductive carbon.
[0023] In some embodiments, at least a portion of the surface of the nano-silicon is coated with conductive carbon to improve the conductivity of the nano-silicon; the nano-silicon also contains fibrous carbon material to bind the nano-silicon material and play an elastic pinning role, and the fibrous carbon material includes at least one of CNT, carbon fiber, vapor-grown carbon fiber, and branched carbon (such as Ketjen black).
[0024] Figure 3 This is a structural schematic diagram of a certain embodiment, wherein the porous carbon 1 contains closed pores 2 and open pores 3, and the nano-silicon 4 is in the form of particles and filled in the pores of the open pores 3, forming a 3D network interpenetrating structure with the porous carbon 1, thereby ensuring structural stability; in order to improve the conductivity of the nano-silicon, the surface of the nano-silicon 4 is also coated with conductive carbon 7, and fibrous carbon material 8 is also contained between the nano-silicon 4 particles for binding the nano-silicon 4 particles, playing an elastic pinning role, thereby ensuring structural stability; the conductive carbon 7 is coated on the surface of the porous carbon 5 and the surface of the nano-silicon 4, and the ionic conductor material 6 is coated on the surface of the conductive carbon 5.
[0025] Figure 4 This is a structural schematic diagram of another embodiment, wherein the porous carbon 1 contains closed pores 2 and open pores 3, and the nano-silicon 4 is in the form of particles and filled in the pores of the open pores 3; the surface of the nano-silicon 4 is also coated with conductive carbon 7, and fibrous carbon material 8 is contained between the nano-silicon 4 particles; the conductive carbon 7 is coated on the surface of the porous carbon 5 and the surface of the nano-silicon 4, and gathers at the mouth of the open pore 3 to complete the pore sealing, and the ion conductor material 6 is coated on the surface of the conductive carbon 5, and finally spherical silicon-containing particles are formed.
[0026] In some embodiments, taking the mass of the silicon negative electrode material as 100%, the mass of the porous carbon accounts for 5~97.2%; the mass of the silicon particles accounts for 2~80%; the mass of the conductive carbon accounts for 0.5~20%; and the mass of the ion conductor material accounts for 0.3~10%.
[0027] In some embodiments, the Dv50 particle size of the nano-silicon is 1~50nm. If the Dv50 particle size of the nano-silicon material is too small, the material specific surface area is too large, which will cause severe side reactions; if the particle size is too large, the nano-silicon material is not easy to embed into the pores of porous carbon.
[0028] In some embodiments, the nano-silicon comprises silicon (nano-silicon particles), silicon oxide SiO x (0<x<2), silicon alloy (Si-M, such as Si-Sn); the conductive carbon includes at least one of hard carbon, soft carbon, carbon black, graphite, carbon fiber, vapor-grown carbon fiber, carbon nanotubes, and graphene; the ion conductor material includes at least one of aluminum oxide, titanium dioxide, zirconium oxide, vanadium oxide, zinc oxide, cobalt oxide, phosphorus oxide, boron oxide, aluminum metaphosphate, lithium metaphosphate, lithium metaaluminate, cobalt metaphosphate, lithium phosphate, lithium aluminate, lithium fluoride, aluminum fluoride, iron fluoride, aluminum hydroxide, LISICON type solid electrolyte, NASICION type solid electrolyte, perovskite type solid electrolyte, garnet type solid electrolyte, sulfide solid electrolyte, and PEO-based polymer electrolyte. Example
[0029] Example 1
[0030] Nano-silicon dioxide is dispersed in phenolic resin and adjusted to a certain solid content. A pressure cooker is used to evacuate the pressure to ≤-0.095MPa. After 30 minutes, nitrogen is introduced and pressurized to 1MPa to adjust the micropores of the phenolic resin. After the pressurization is completed, the temperature is slowly increased to 160°C at 0.5°C / min and kept for 5 hours to complete the resin curing. During the heating process, the pressure is continuously released to maintain a stable pressure. The cured resin is heated and carbonized in a resistance furnace at a heating rate of 1°C / min and a carbonization temperature of 1000°C. After the resin is carbonized, it is crushed using a jet mill to control Dv50=10um. After the powder is crushed, it is etched in a static bed with HF as the etchant to remove the nano-silicon dioxide. After completion, it is rinsed and dried with deionized water to complete the preparation of porous carbon.
[0031] The porous carbon was heated to 500℃ in a rotary kiln, and 3% volume concentration of silane was introduced, and the diluent gas was hydrogen. In order to allow the gas to enter the porous carbon pores and improve the gas utilization rate, the gas was introduced by pulse method, and the pressure was controlled to be 0~0.05MPa. The reaction time was 240min, so that nano-silicon was deposited on the surface of the porous carbon pores; then the temperature was raised to 700~850℃, 5~30% volume concentration of acetylene was introduced, and the diluent gas was argon. The reaction time was 1~4h, and a layer of conductive carbon was coated on the surface of the nano-silicon; then the temperature was raised to 850~1100℃, 5~30% volume concentration of acetylene was introduced, and the diluent gas was argon. The reaction time was 1~4h, and conductive carbon was generated at the opening and the outer surface to complete the sealing. The permeation coating and surface coating can be controlled by adjusting the reaction temperature. The reaction rate at low temperature is low, and the gas can penetrate into the pores. The reaction rate at high temperature is high, and the gas reacts on the surface to complete the sealing and coating.
[0032] The above-mentioned conductive carbon-coated powder and lithium metaphosphate are dispersed in a PAA-Li solution, and are evenly mixed to prepare a slurry with a solid content of 35%. The powder is dried using a spray dryer, and the aluminum metaphosphate is dispersed and bonded on the porous carbon surface to prepare the silicon negative electrode material.
[0033] Example 2
[0034] The porous carbon was prepared in the same manner as in Example 1.
[0035] Silicon powder is ground in an ethanol solvent until D50 is less than 50nm to prepare a nano-silicon slurry, and carbon nanotubes are added and then further ground and dispersed to prepare a nano-mixed slurry of nano-silicon and carbon nanotubes; porous carbon is dispersed in the nano-mixed slurry of nano-silicon and carbon nanotubes, and then a solvent is added to dilute it to control the solid content to 22%; the slurry is subjected to vacuum and pressure impregnation in a pressure autoclave to allow most of the nano-mixed slurry to enter the pores of the porous carbon: evacuate to a pressure of ≤-0.095MPa for 30 minutes, then introduce nitrogen and pressurize to 4MPa, maintain the pressure for 2 hours, and then release the pressure to complete the impregnation, so that the nano-silicon is filled in the pores of the porous carbon; the slurry that has undergone vacuum and pressure impregnation is separated into solid and liquid by a centrifuge, and the nano-slurry that has not entered the pores is removed; and the filter cake is air-dried using an air-flow dryer. The dried powder is heated to 950°C in a rotary kiln, and 10% volume concentration of acetylene is introduced, and the diluent gas is argon. The reaction time is 90 minutes, and a layer of conductive carbon is coated on the surface of nano-silicon and porous carbon. The above-mentioned powder coated with conductive carbon and aluminum sol are dispersed in water, and prepared into slurry after uniform mixing. The slurry solid content is 35%, and a spray dryer is used to prepare the powder; finally, the powder coated with aluminum hydroxide is sintered in a rotary kiln at a sintering temperature of 700°C and a holding time of 2 hours to convert aluminum hydroxide into aluminum oxide. After sintering, the silicon negative electrode material is prepared.
[0036] Embodiment 3-4
[0037] The other steps and process parameters are the same as those in Example 1, except that the proportion of the number of openings and the volume proportion of the openings in the range of 200-1000 nm are different. The number and diameter of open and closed pores can be adjusted by adjusting the silica Dv50 particle size, the weight ratio of silica and phenolic resin, and the reaction pressure and solid content. However, the proportion of the number of openings and the volume proportion of the openings in the range of 200-1000 nm are still within the scope required by the present application.
[0038] Comparative Examples 1 to 4
[0039] The other steps and process parameters are the same as those in Example 1, except that the proportion of the number of openings and the volume proportion of the openings in the range of 200 to 1000 nm are different. The number and diameter of open and closed pores can be adjusted by adjusting the silica D50 particle size, the weight ratio of silica and phenolic resin, and the reaction pressure and solid content, so that the proportion of the number of openings and the volume proportion of the openings in the range of 200 to 1000 nm are outside the required range of this application.
[0040] The following method was used to evaluate the performance of the silicon negative electrode material prepared in each embodiment.
[0041] Open and closed pore quantity test: low carbon residue resin is used as the mounting resin sample, polished, and then the mounting resin is ablated clean under an inert protective atmosphere to obtain a test sample. The open and closed pore data are counted through a metallographic microscope system.
[0042] Porosity, pore size and proportion testing method: using mercury intrusion instrument or BET specific surface area tester.
[0043] Nano silicon particle size test method: Observe the nano silicon particles through a field emission scanning electron microscope or a transmission electron microscope, directly measure the particle sizes of 5-10 nano silicon particles through a scale, and take the average value of the particle size as the final nano silicon particle size.
[0044] The negative electrode material obtained in the embodiment was assembled into a button half-cell according to the conventional method, and its electrochemical performance was tested: the prepared negative electrode material powder: SP (carbon black): CNT (carbon nanotube): PAA (polyacrylic acid) was mixed in a mass ratio of 80:9:1:10, and an appropriate amount of deionized water was added as a solvent, and the mixture was stirred continuously for 8 hours with a magnetic stirrer until it became a paste. The stirred slurry was poured on a copper foil with a thickness of 9 μm, coated with an experimental coating machine, and dried at 85°C under vacuum (-0.1 MPa) for 6 hours to obtain a negative electrode sheet. The electrode sheet was rolled to 100 μm on a manual roller machine, and then a disc with a diameter of 12 mm was obtained with a punching machine, dried at 85°C under vacuum (-0.1 MPa) for 8 hours, and weighed and the weight of the active material was calculated. CR2032 button cells were assembled in a glove box using lithium metal sheet as the counter electrode, polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 in EC:DEC=1:1 Vol% with 5.0%FEC as the electrolyte.
[0045] Initial specific capacity: The battery was charged and discharged using the LAND battery test system. After standing for 6 hours, it was discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V. After standing for 5 minutes, it was charged at a constant current of 0.05C to 1.5V. The charge specific capacity obtained at this time is the initial specific capacity of the material.
[0046] First full charge expansion rate test: CR2032 button cells were prepared using the above method, and the battery was charged and discharged using the LAND battery test system. After standing for 6 hours, the battery was discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V. The button cells were disassembled in the glove box, and the thickness of the electrode was measured. The expansion rate was calculated as follows: (thickness of the electrode after the cycle - thickness of the fresh electrode) / thickness of the fresh electrode × 100%.
[0047] Cycle performance test: The battery was charged and discharged using the LAND battery test system. After standing for 6 hours, it was discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V; after standing for 5 minutes, it was charged to 1.5V at 0.05C constant current; after standing for 5 minutes, the above steps were repeated twice; then it was discharged to 0.005V at 0.25C; after standing for 5 minutes, it was charged to 1.5V at 0.25C constant current. The battery cycle performance was tested for 20 times, and the capacity retention rate was calculated by dividing the charging capacity of the 20th cycle / the charging capacity of the 1st cycle × 100%.
[0048] Rate performance test: The button cell was left at room temperature for 12 hours, and then tested with constant current charge and discharge on the Blue Electric test system. The charge and discharge cut-off voltage was 3.0~4.25V. First, charge and discharge at 0.1C current for 3 cycles. Then charge and discharge at 0.5C current for 3 cycles. Finally, the ratio was obtained by calculating the specific capacity measured at 0.5C / 0.1C specific capacity × 100%. The higher the ratio, the better the rate performance.
[0049] Table 2 Comparison of the performance of negative electrode materials prepared in various embodiments
[0050] sample Opening ratio The proportion of opening diameters between 200 and 1000 nm First full charge expansion rate Capacity retention rate 0.5C specific capacity / 0.1C specific capacity Example 1 80% 50% 55% 90% 85% Example 2 80% 50% 55% 89% 86% Example 3 85% 75% 63% 85% 90% Example 4 99.9% 80% 70% 85% 90% Comparative Example 1 50% 80% 55% 75% 80% Comparative Example 2 100% 50% 77% 80% 85% Comparative Example 3 80% 20% 60% 75% 80% Comparative Example 4 99.9% 90% 80% 70% 75%
[0051] The test results of the silicon negative electrode materials prepared in each embodiment and comparative example are shown in Table 1. The difference between Example 1 and Example 2 is that in Example 1, the nano-silicon is loaded on the pore wall of the open hole, and in Example 2, the nano-silicon is filled in the pore of the open hole. From the test results of Example 1 and Example 2, the performance of the negative electrode materials with nano-silicon in different positions is similar. The data from Example 1 and Examples 3 to 4 show that the negative electrode material with the best electrical performance can be obtained by optimizing the ratio of the number of openings and the size and ratio of the pores. From the data of each embodiment and comparative example, the silicon negative electrode material provided in the present application has a low expansion rate and has a good capacity retention rate and rate performance. It can be seen from the data of Comparative Example 2 that the presence of an appropriate amount of closed pores helps to alleviate volume expansion.
[0052] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the above description is not a limitation of the invention, and the present invention is not limited to the specific embodiments disclosed and described above. Some modifications and changes to the invention, such as changes, modifications, additions or substitutions made by those skilled in the art within the essential scope of the embodiments to the equivalent replacement of each raw material and the addition of auxiliary components, the selection of specific methods, etc., should also fall within the scope of protection of the claims of the present invention.
Claims
1. A low expansion silicon negative electrode material, comprising porous carbon, nano silicon, conductive carbon and ion conductor material, characterized in that: The pores of the porous carbon include open pores and closed pores; taking the total number of the open pores and the closed pores as 100%, the number of the open pores accounts for 80-99.9%; The pore diameter of the opening is 50-1000 nm, wherein, taking the total volume of the opening as 100%, the pore diameter of the opening accounting for 50-80% of the volume is 200-1000 nm; The nano-silicon covers at least a portion of the pore walls of the open pores and at least a portion of the surface of the porous carbon; the conductive carbon covers at least a portion of the surface of the nano-silicon; the ion conductor material covers at least a portion of the conductive carbon, Or, the nano-silicon is filled in the open pores; The conductive carbon covers at least a portion of the surface of the porous carbon; and the ion conductor material covers at least a portion of the conductive carbon.
2. The silicon negative electrode material according to claim 1, characterized in that The porosity of the porous carbon is 2-95%.
3. The silicon negative electrode material according to claim 1, characterized in that: At least a portion of the surface of the nano-silicon is coated with conductive carbon; the nano-silicon also contains fibrous carbon material, and the fibrous carbon material includes at least one of CNT, vapor-grown carbon fiber, and branched carbon.
4. The silicon negative electrode material according to claim 1, characterized in that: Taking the mass of the silicon negative electrode material as 100%, the mass of the porous carbon accounts for 5-97.2%; the mass of the nano-silicon accounts for 2-80%; the mass of the conductive carbon accounts for 0.5-20%; and the mass of the ion conductor material accounts for 0.3-10%.
5. The silicon negative electrode material according to claim 1, characterized in that: The Dv50 particle size of the nano-silicon is 1-50 nm.
6. The silicon negative electrode material according to claim 1, characterized in that: The nano-silicon includes at least one of silicon element, silicon oxide SiOx, and silicon alloy, wherein 0<x<2; the conductive carbon includes at least one of hard carbon, soft carbon, carbon black, graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; the ion conductor material includes at least one of aluminum oxide, titanium dioxide, zirconium oxide, vanadium oxide, zinc oxide, cobalt oxide, phosphorus oxide, boron oxide, aluminum metaphosphate, lithium metaphosphate, lithium metaaluminate, cobalt metaphosphate, lithium phosphate, lithium aluminate, lithium fluoride, aluminum fluoride, iron fluoride, aluminum hydroxide, LISICON type solid electrolyte, NASICION type solid electrolyte, perovskite type solid electrolyte, garnet type solid electrolyte, sulfide solid electrolyte, and PEO-based polymer electrolyte.
Citation Information
Patent Citations
High-conductivity silicon-oxygen negative electrode material and application thereof
CN111048756A
Silicon-containing negative electrode material for lithium ion battery and preparation method of silicon-containing negative electrode material
CN111755683A